2021
DOI: 10.1177/20587392211047303
|View full text |Cite
|
Sign up to set email alerts
|

Patients who are admitted to the Department of Internal Medicine with a very low C-reactive protein concentration

Abstract: Introduction C-reactive protein (CRP) is a marker commonly used in clinical practice as a reference for the inflammatory activity in vivo. Low levels are often associated with good health and lower risk for adverse outcomes. Patients and methods We examined medical records of the last 6 years, of all patients admitted for hospitalization in internal medicine wards who had the first CRP measurement below ≤ 0.03 mg/L (detection limit). Diagnosis criteria and 7 days’ survival were reviewed. Results Out of 61,590 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It was found, indeed, that despite presenting with a relatively low-grade inflammatory response that could potentially be observed in an apparently healthy population, these individuals might harbor severe and potentially lethal medical conditions. This concept was recently described by our group in patients who were admitted to the hospital with CRP concentrations that were below the detection level of the wr-CRP test [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found, indeed, that despite presenting with a relatively low-grade inflammatory response that could potentially be observed in an apparently healthy population, these individuals might harbor severe and potentially lethal medical conditions. This concept was recently described by our group in patients who were admitted to the hospital with CRP concentrations that were below the detection level of the wr-CRP test [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, repeated measures of inflammatory biomarkers are more informative than looking at a single snapshot. We have recently shown that patients who are admitted with very low CRP concentrations do not necessarily present a benign course of their disease [ 3 ]. In addition, we could show that a follow-up CRP test could add significant prognostic information to the medical team [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data were obtained using MDClone (mdclone.com), a query tool that provides comprehensive patient-level data of wide-ranging variables in a defined timeframe around an index event. The MDClone system is a patient-level data extraction system designed to ease the query of large medical records [ 25 ]. Each patient admitted to the hospital upon arrival to the emergency department (ED) underwent basic inflammatory biomarkers assessment including complete blood count (CBC) and C-reactive protein.…”
Section: Methodsmentioning
confidence: 99%
“…All of these studies manifest that despite presenting with a relatively low-grade inflammatory response that could potentially be observed in an apparently healthy population, these patients might harbor severe and potentially lethal medical conditions, which might be overlooked by the treating physician upon clinical presentation in light of the apparently normal first CRP measurement. Further strengthening this concept was a recent study of patients admitted with a very low C-reactive protein concentration [ 25 ]. These findings strongly suggested not relying on a single apparently normal CRP concentration upon admission to a medical facility but insisting on at least one, if not more than one, additional test to follow.…”
Section: Using Crp Dynamics In the Diagnosis Of Infectious Diseasesmentioning
confidence: 99%